2017
DOI: 10.1002/cc.20279
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Transfer Mission and Student Mobility

Abstract: This chapter explores the changing nature of how students experience postsecondary education that results in a considerable amount of “swirl” between institutions. Although the traditional notion of “vertical” transfer from a community college to a university continues to be an important aspect of the community college mission, the varying patterns of mobility between institutions will have significant implications for students, the costs they incur, and their ultimate success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Using the Beginning Postsecondary Students 96:01 data, Peter et al (2005) showed that about 13.3% of students who started at community colleges across the United States transferred to another community college, while another 24% of community college students transferred to a 4-year university. Citing National Student Clearing House reports, Baldwin (2017) showed that more than one-third of community college students across the country transferred to another community college. Among those who started within the North Carolina Community College System, the percentage of lateral transfer students was about 13%, which was as large as the percentage of vertical transfer students (Yang et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Beginning Postsecondary Students 96:01 data, Peter et al (2005) showed that about 13.3% of students who started at community colleges across the United States transferred to another community college, while another 24% of community college students transferred to a 4-year university. Citing National Student Clearing House reports, Baldwin (2017) showed that more than one-third of community college students across the country transferred to another community college. Among those who started within the North Carolina Community College System, the percentage of lateral transfer students was about 13%, which was as large as the percentage of vertical transfer students (Yang et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Community college students pursue various academic goals (a certificate, associate degree, or bachelor’s degree), and some of them do not pursue a credential at all but attend college for lifelong learning purposes (AACC, 2021; Cohen et al, 2013). Community colleges accommodate these various needs by offering different types of programs and degrees (Baldwin, 2017; Taylor & Jain, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education has often defined a transfer student as one who has attended more than one institution (Adelman, 2006; Dougherty & Kienzl, 2006). While this has often been seen as a one‐time event from a single institution into another institution to receive a credential, students are often “swirling” among several institutions (Baldwin, 2017). This growing trend has many benefits to students and it can allow for a great deal of flexibility in taking courses that are needed.…”
Section: Types Of Transfer Students—the Complexity Of College Student...mentioning
confidence: 99%